S3A:4 Ox40/ox40l axis impairs follicular and natural regulatory t cell function in human systemic lupus. (21st March 2018) - Richez, C; Augusto, JF; Lazaro, E; Gensous, N; Douchet, I; Contin-Bordes, C; Blanco, P
Abstract : The mechanisms responsible for the Treg deficiency in SLE remain unclear. Our group recently reported that OX40L stimulation induces CD4 +T cells to express T follicular helper cells (TFH) associated molecules, and is sufficient to induce CD4 +T cells to become functional B cell helpers. We hypothesised that OX40L/OX40 axis was implicated in Treg and regulatory follicular helper T cell (TFR) dysfunction in SLE. Methods: Flow cytometry was used for analysis of SLE patients (n=61) and healthy donors (HD) (n=16). Using recombinant sOX40L, in vitro -generated SLE-DCs expressing OX40L, and DCs from patients, the impact of OX40/OX40L axis on the function of cTregs (CD4 +CXCR5-CD25high Foxp3+) and TFR (CD4 +CXCR5+CD25 high Foxp3+) purified from HD was studied. Results: OX40L/OX40 axis engagement on Tregs and TFR not only specifically impaired their ability to regulate T effector cells proliferation but also their ability to suppress TFH-dependent B cell activation, and immunoglobulin secretion. Indeed, we observed that soluble and membrane-bound OX40L decreased suppressive Treg function (p<0.05), without inducing Treg cell death. Treg suppressive function was restored when in vitro -generated SLE-DCs expressing OX40L were pre-incubated with a blocking anti-OX40L mAb. Furthermore, purified tonsils TFR cells previously cultured or not with sOX40L were cultured with purified TFH and memory B cells in the presence of SEB. We observed higher immunoglobulin production and increased differentiation of B cells into CD38 +plasmablasts in co-cultures with TFR exposed to sOX40L. APCs from active SLE patients (n=5) mediated Tregs dysfunction in an OX40L-dependent manner (p=0.01). We also observed an inverse correlation between OX40L expression on SLE-APCs and their ability to hamper Tregs cell suppressive function (r=−0.85, p=0.0001). OX40L-expressing cells co-localised with FoxP3 positive cells in active SLE skin lesions, suggesting that OX40L+cells Treg contact actually operates in vivo within inflammatory tissues. In vitro, engagement of OX40L/OX40 axis resulted in FoxP3 down-regulation in Tregs. FoxP3 expression in SLE Tregs negatively correlated with the proportion of circulating OX40L-expressing mDCs, suggesting that OX40L-dependent Foxp3 down-regulation also operates in vivo . Conclusion: These data support that OX40L/OX40 signals are implicated in T regulatory cell dysfunction in SLE. Blocking OX40L/OX40 axis appears as promising therapeutic strategy.